PENGARUH DETERMINAN PERAN DOSEN TERHADAP MUTU PERGURUAN TINGGI SWASTA DI KOTA MEDAN - Lilik Hidayat Pulungan; Elfrianto , (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2017)
Determinant Effect of Lecturers’ Roles in Quality Assurance in Higher Education. This study aims to (1) find out an empirically tested model of determinant factors of lecturers’ roles in quality assurance in higher education, and (2) investigate contributions of leadership, organization culture, lecturers’ competence, and achievement motivation as individual variables and an aggregate to lecturers’ roles in quality assurance. The sample consisted of 206 lecturers of private universities in the area of Kota Medan, selected by the proportional random technique. The data were collected through questionnaires and analyzed by the SEM technique. The results show that, first, the goodness of fit exists between the conceptual model and the empirically tested model (p-value 0.34 > 0.05 and RMSEA 0.01 < 0.05); second, the contributions of leadership, organization culture, lecturers’ competence, and achievement motivation to quality assurance are, respectively, 28.09%, 50.41%, 8.41%, and 5.29%; third, the contribution of the variables as an aggregate is 95%. This implies that to improve lecturers’ roles in quality assurance in higher education, it is necessary to develop visionary leadership, firm organization culture, competent lecturers’ support, and high achievement motivation.Keywords : leadership, organization culture, competence, achievement motivation, lecturers’ roles